Analysis The Relationship Between Vietnam’s Direct Investment and GDP Growth of Lao PDR - SITTHIPHONE, Manichanh; CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper aims to analysis the relationship between Vietnam’s Direct Investment and GDP Growth of Lao PDR, with the variable of the economic growth of Lao PDR (lnGDP) and Vietnam’s Direct Investment (lnFDIVN), as a time series from 2001-2023, focusing on the analysis using the regression model with the ordinary least squares method and analysis the correlation of the short-run by the method of VECM, the long-run by cointegration method and Granger causality test. The results found that: The regression model show that the coefficient of lnFDIVN is positive values and rejects null hypothesis with a statistical significance level of 0.01, indicating that the foreign direct investment of Vietnam has a positive effect on the economic growth of Lao PDR. The results of the short-run correlation by the vector error correction model (VECM) shows that the value of the Error Correction Term (ECT) is equal to - 0.13157 which is between]-1; 0[and rejects null hypothesis with a statistical significance level of 0.05, it shows that when there is an positive or negative economic shocks, the relationship between Vietnam's direct investment and the economic growth of Lao PDR in the short-run will adjust to a long-run equilibrium with an adjustment speed equal to 13.157%. The results of the long-run correlation by the by the cointegration test shows that the coefficient value is positive and rejects the main hypothesis with a statistical significance level of 0.05. It shows that Vietnam's direct investment and economic growth Lao PDR have a positive long-run relationship with a 95% confidence level. For the granger causality test, the null hypothesis is rejected with a statistical significance level of 0.01 meaning there is only unidirectional relationship where the economic growth of Lao PDR to Vietnam's direct investment.